Studies of Stock Pricing in China Small and Medium-sized Board -Based on CAPM and Three-Factor Model - LI, QINGTAO (2017)
Abstract Small and Medium-Sized Board was built in China in 2004. As a crucial role in main-board market, it builds a multi-level capital market and to support the development of small and medium-sized enterprises. However, there is still few empirical study of the empirical research of the growth enterprise market in China. It also is important in both practice and theory for researching in asset pricing theory. This dissertation uses some western theoretical models and research findings to study, and to find an effective and practical pricing model in the small and medium-sized board model, which helps investors to make decision. This paper makes a systematic analysis and summarization about the Capital Asset Pricing Model and the Three-Factor pricing model. Depends on the theoretical model analysis, this paper empirically tests determinants of the yield of the risky assets in small and medium-sized board. And empirical tests shows that CAPM is not effective, since there is no relationship between stock return and beta. While three-factor pricing model has high fitting level and applicability in small and medium-sized board. Moreover, we find the small company effect in this type of board